Antibodies Against Angiotensin II Receptor Type 1 and Endothelin A Receptor Are Associated With an Unfavorable COVID19 Disease Course - Miedema, Jelle; Schreurs, Marco; van der Sar – van der Brugge, Simone; Paats, Marthe; Baart, Sara; Bakker, Marleen; Hoek, Rogier; Dik, Willem Arnout; Endeman, Henrik; Van Der Velden, Vincent; van Gammeren, Adriaan; Ermens, Antonius; et al. (Frontiers in Immunology, 2021)
Background Lung histopathology demonstrates vasculopathy in a subset of deceased COVID19 patients, which resembles histopathology observed in antibody-mediated lung transplant rejection. Autoantibodies against angiotensin II type 1 receptor (AT1R) and Endothelin receptor Type A (ETAR) have been demonstrated in antibody-mediated rejection and may also be associated with severe COVID19 infection. Objective To assess AT1R and ETAR auto-antibodies in COVID19 patients and controls, and explore their association with disease course. Methods 65 hospitalized patients with COVID19 infection were included. Clinical and laboratory findings were retrospectively assessed. Patients with unfavorable disease course, admitted at the intensive care unit and/or deceased during hospital admission (n=33) were compared to admitted COVID19 patients with favorable disease course (n=32). The presence of antinuclear antibodies (ANA) and auto-antibodies against AT1R or ETAR in peripheral blood were compared between COVID19 with unfavorable and favorable disease course and age matched controls (n=20). Results The presence of ANA was not significantly different between COVID19 patients with unfavorable (n=7/33; 21%) and favorable disease course (n=6/32; 19%) (p= 0.804) and controls (n=3/20; 15%). Auto-antibodies against AT1R were significantly increased in unfavorable disease course (median 14.59 U/mL, IQR 11.28 – 19.89) compared to favorable disease course (median 10.67 U/mL, IQR 8.55 – 13.0, p< 0.01). ETAR antibody titers were also significantly increased in unfavorable disease course (median 7.21, IQR 5.0 – 10.45) as compared to favorable disease course (median 4.0, IQR 3.0 – 6.0, p <0.05). Conclusion Auto-antibodies against AT1R and ETAR are significantly increased in COVID19 patients with an unfavorable disease course.